Appication of Numerical Simulations to the Study of Spread and Control of COVID-19 in Nigeria - Ebelechukwu, Okorie Charity; Yusuf, Haruna; Abdulhamid, Bala Ma’aji; Danladi, Hina Aliyu (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Corona virus is a disease that started by putting human being into the state of fear. It is the most dreaded disease that created an indelible mark that all the countries in the world cannot forget in a hurry. The emergency of COVID-19 motivated the researchers into carrying out research work so as to see if there is a way to control its spread thereby preventing the incessant death associated with COVID-19. From the literatures, we observed that some areas have been covered but we observed that quarantine, vaccination and partial immunity were not covered. This prompted this research. The aim is to determine the impact of vaccination and partial immunity on the transmission dynamics of COVID-19. To achieve this, we carried out numerical simulation so as to find out if quarantine, vaccination and partial immunity have impact in the spread and control of COVID-19, using the data we obtained from National Centre for Disease Control, World Meters and from Literatures The analysis was carried with the aid of Maple 2023 software. The results show that quarantine, vaccination and partial immunity has impact in the spread and control of COVID-19. We therefore recommend that incomplete doses of the vaccines should be avoided for effective control of the disease. Health workers should ascertain the health condition of a patient before discharging such patients so as to prevent partial immunity.